Very rare giant adrenal myelolipoma: a tumor mimic - Padhy, Aditya Prasad; Kanungo, Abinash; Das, Deepak Kumar; ., Sunny (International Surgery Journal, 2020)
Adrenal myelolipoma is a very rare benign neoplasm usually unilateral, and nonsecreting, occurring in the adrenal gland which consist of fatty tissues and hematopoietic elements. Some cases of this type may cause symptoms like chronic abdominal pain however usually these tumors are small and asymptomatic. Surgery is the modality of treatment where there are severe symptoms with life threatening progression with size of tumor reaching more than 6 cm. Here we report an unusual case of a 59-year-old male with history of chronic abdominal pain from a growing right-sided large adrenal mass. With all possible hematological, histo-pathological as well as imaging investigations warranted a high suspicion for tumor mass, hence decided for surgically excision, which was both diagnostic as well as curative. The histopathological study of the excised mass confirmed the initial diagnosis of adrenal myelolipoma. Surgery is the diagnostic and curative modality of treatment for adrenal myelolipoma after all possible investigations to reach for a clinical diagnosis as well for proper planning for surgery. By this we can prevent complications like spontaneous rupture and hemorrhage of the mass, and subsequent cardiovascular shock. Management varies from individual to individual. Open radical adrenalectomy is the standard treatment for giant myelolipomas (size >10 cm), while the minimally invasive approach has been used in only few cases of small sized tumors. Although it is a benign tumor, surgery plays main role for symptomatic cases and high suspicion of malignancy.